Experimental and theoretical study of the compound [Pd(dmba)(NCO)(imz)] - Treu-Filho, Oswaldo; Pinheiro, Jose C.; da Costa, Edson B.; Ferreira, Joao E. V.; de Figueiredo, Antonio F.; Kondo, Rogerio T.; de Lucca Neto, Vicente A.; de Souza, Rodrigo A.; Legendre, Alexandre O.; Mauro, Antonio E. (Elsevier B.V., 2007)
The compound [Pd(dmba)(NCO)(imz)] (dmba = N,N-dimethylbenzilamine; NCO = cyanate; imz = imidazole) was studied through experimental and theoretical methods. The complex was synthesized and characterized by IR and NMR spectroscopy. To an appropriate representation of the molecular environment, Gaussian basis sets for the constituent atoms of the compound were built and, after adequate supplementation with polarization and diffuse functions, they were used to study the molecule. Calculations of electronic and vibrational structure of two possible isomers were carried out, showing that the compound, which contains the NCO GROUP trans to the Pd-C bond, is 4.29 kcal/mol more stable than the analogous one, where the imz ligand is trans to the Pd-C bond. The calculated molecular parameters, bond distances, and bond angles showed that the geometry around the metallic center is square-planar with the cyanate being linear. The theoretical infrared spectrum of C(1) symmetry (electronic state (1)A) is in accordance with the experimental one. It also verified the contribution of Pd (4d(xz) + 4d(yz)) and Pd (4d(xy)) in the HOMO and LUMO orbitals, respectively. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: GCHF method; DFT; total atomic charges; infrared spectroscopy; palladium